Case report: A novel mutation in RTEL1 gene in dyskeratosis congenita - Nisar, Haider; Khan, Memoona; Chaudhry, Qamar Un Nisa; Iftikhar, Raheel; Ghafoor, Tariq (Frontiers in Oncology, 2023)
Dyskeratosis congenita (DKC), also known as Zinsser-Cole-Engman syndrome, is a telomeropathy which typically presents as a triad of leukoplakia, nail dystrophy and reticular hyperpigmentation. Genes responsible for the disorder and reported in the literature include DKC1, TINF2, TERC, TERT, C16orf57, NOLA2, NOLA3, WRAP53/TCAB1, and RTEL1. Homozygous, compound heterozygous and heterozygous mutations in RTEL1 (RTEL1, regulator of telomere elongation helicase 1) gene on chromosome 20q13 are known to cause autosomal dominant as well as recessive DKC. Some of the pathogenic variants of RTEL1 reported in literature are c.2288G>T (p.Gly763Val) and c.3791G>A (p.Arg1264His) and RTEL p.Arg981Trp. We report a novel homozygous variant of RTEL1 c.2060C>T (p. Ala687Val) in a patient of DKC presenting with leukoplakia, dystrophic nails, reticulate pigmentation and positive family history of similar phenotype. The novel variant, reported as variant of uncertain significance, may therefore be considered pathogenic and updated in the genetic data base.